2009
DOI: 10.1016/j.jana.2009.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Sexual HIV Transmission Among Wives Left Behind and Wives of Nonmigrant Men in Rural Areas of China

Abstract: In rural areas of China where commercial plasma donation used to be common, little is known about sexual behaviors and condom use among wives left behind by migrating husbands and wives of nonmigrant men. This study investigated sexual behaviors and condom use among married women in rural areas of China. A cross-sectional survey was conducted with 1,873 participants recruited by a cluster-sampling method. Study results showed that wives left behind had a significantly lower mean frequency of sexual intercourse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 15 publications
(19 reference statements)
1
14
0
Order By: Relevance
“…Sixty-three percent (61 of 97) of the studies collected data on labor migrants while they were away from home and 21 % (20 of 97) upon their return to their place of usual residence. Of the remaining studies, 8 % (6 of 97) studied labor migrants while they were in transit, 4 % (4 of 97) collected data in both sending and receiving places [3638] and only one study surveyed the wives of migrants left behind at the sending place [39]. Internal migration was more heavily represented among the Western Pacific data (22 of 23; 96 %), reflecting high research interests in the large floating population in China, while studies on external migration predominated in the Americas (21 of 22; 95 %).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sixty-three percent (61 of 97) of the studies collected data on labor migrants while they were away from home and 21 % (20 of 97) upon their return to their place of usual residence. Of the remaining studies, 8 % (6 of 97) studied labor migrants while they were in transit, 4 % (4 of 97) collected data in both sending and receiving places [3638] and only one study surveyed the wives of migrants left behind at the sending place [39]. Internal migration was more heavily represented among the Western Pacific data (22 of 23; 96 %), reflecting high research interests in the large floating population in China, while studies on external migration predominated in the Americas (21 of 22; 95 %).…”
Section: Resultsmentioning
confidence: 99%
“…Family separation due to migration also effected wives who were left behind by their husbands. In comparing Chinese wives of migrants to Chinese wives of non-migrant men, migrants’ wives had higher rates of multi-partnering, higher rates of HIV infection and lower rates of condom use [39]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Studies in Africa and Asia demonstrated that female partners of male migrants are also at higher risk of HIV infection. [5][6][7] As of July 2015, 26,702 cases of HIV were reported in Nepal. 8 The total number of HIV infection was estimated to be 39,249 and adult HIV prevalence was 0.2%.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown wives residing in sending countries have higher rates of HIV infection, largely, due to their husbands’ increased sexual risk behaviors (Grawert, 1992; Lurie et al, 2003; Qin et al, 2009; Shah, Khan, Kristensen, & Vermund, 1999; Zuma, Gouws, Williams, & Lurie,2003). The system of gender roles transforming men into labor migrants contributes to wives' vulnerability to HIV/AIDS.…”
Section: Introductionmentioning
confidence: 99%